A Review of Evolution of Learning and Memory Mechanisms (1st Ed) - Bertin, Francisca (Revista de Psicología, 2022)
Editors: Mark A. Krause, Karen L. Hollis, & Mauricio R. PapiniPublisher: Cambridge University PressPlace of publication: Cambridge, UKYear: 2022Online ISBN: 9781108768450https://doi.org/10.1017/9781108768450Publisher details: Dr. Mark A. Krause is Professor of Psychology at Southern Oregon University. He has studied various psychological processes of learning in multiple animals, including birds, chimpanzees, and snakes. He worked as an associate editor at the Journal of Animal Behavior and Cognition. Dr. Karen. L. Hollis is Professor Emeritus of Psychology at Mount Holyoke College. She stands out for her studies in multiple species integrating animal learning under an evolutionary perspective. She has worked as an editor for Animal Learning & Behavior, Journal of Comparative Psychology, Psychonomic Bulletin & Review and Behavioral Processes. Dr. Mauricio R. Papini is Professor of Psychology at Texas Christian University. He works on the comparative study of the associative and emotional modulation of behavior in different vertebrates. He is also an editor at the International Journal of Comparative Psychology.